Caracterización de pacientes y de uso de medicamentos en un grupo de adultos mayores asistentes a una actividad promocional de geriatría - Rojas G., Myrna; Ruiz A., Inés; Carrasco M., Víctor Hugo; Molina Y., Juan Carlos (Revista Hospital Clínico Universidad de Chile, 2008)
Study objectives: To establish frequency of polypharmacy, proportion of use of drugs without prescriptions, and personal mean monthly expenditure on drugs among elderly people attending to a promotional activity on geriatrics at the Hospital Clínico de la Universidad de Chile. Methods: Observational study that analyses answers given by 235 elderly people who attended to thepromotional activity on geriatrics. Results: The 99.6% interviewees lived in the Metropolitan Region, 82.6% were females, a big number of them had ages between 60 and 69 years. The 63.8% were affiliated to the public secure of heath (FONASA). The 41.6% of those nonaffiliated to FONASA expended between 10,000 and 50,000 Chilean pesos by month to buy drugs. The 32.3% received polypharmacy (≥ 5 drugs), and 17.4% of interviewees used auto-prescribed drugs. It was observed a greater frequency of auto-indicated drugs among women (34%) than men (24.4%). The 235 interviewees communicated a total of 857 diseases (3.64 ± 1.89 diseases/patient), being arterial hypertension the most frequent one (19.1%). Conclusion: It seems important to develop other type of studies in Chile that permit to establish frequency of polypharmacy among elderly people, and its outcomes on health quality of life, clinical and economic conditions.